Читаем детям: стихи, сказки, рассказы, басни / худож. С. Сачков, Е. Шурлапова, С. Подивилов - Сачков Сергей Николаевич (Родители читают детям, 2003)
Экземпляры: аб. (2005) / Инвентарный номер: 48421 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: Ч-69 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)